2002
DOI: 10.1039/b207652g
|View full text |Cite
|
Sign up to set email alerts
|

Assignment of absolute configuration of a chiral phenyl-substituted dihydrofuroangelicin

Abstract: A phenyl-substituted chiral dihydrofuroangelicin, 4-methyl-8-(2-E-phenylethenyl)-8,9-dihydro-2H-furo[2,3-h]- 1-benzopyran-2-one, synthesized in racemic form, has been resolved by HPLC chiral separation, and its absolute configuration determined by the non-empirical exciton chirality method. The solution conformation has been investigated through NMR and molecular modeling methods: two minima found by molecular mechanics and DFT methods are in keeping with observed 1H-1H 3J coupling constants and NOE effects. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 21 publications
3
14
0
Order By: Relevance
“…This conclusion was fully confirmed by a DeVoe calculation: employing 41 standard spectroscopic parameters for the coumarin and styrene transitions and the minimum energy structure found for the (S) enantiomer, a positive couplet, having A = +11.7 was calculated, in full agreement with the experimental one, having A = +15.7.…”
Section: Latest Applications Of the Devoe Approachsupporting
confidence: 70%
See 1 more Smart Citation
“…This conclusion was fully confirmed by a DeVoe calculation: employing 41 standard spectroscopic parameters for the coumarin and styrene transitions and the minimum energy structure found for the (S) enantiomer, a positive couplet, having A = +11.7 was calculated, in full agreement with the experimental one, having A = +15.7.…”
Section: Latest Applications Of the Devoe Approachsupporting
confidence: 70%
“…Coupled oscillator calculations have been very recently employed 41 to assign the absolute configuration of a new chiral dihydrofuroangelicin, 4-methyl-8-(2-E-phenylethenyl)-8,9-dihydro-2H-furo[2,3-h]-1-benzopyran-2-one (12) (Chart 6). Compound 12 was prepared in racemic form and the enantiomers of 12 were resolved by HPLC upon the chiral stationary phase Chirobiotic T. The most retained enantiomer of 12 showed in the UV spectrum (between 400 and 200 nm) two main regions of absorption ( Fig.…”
Section: Latest Applications Of the Devoe Approachmentioning
confidence: 99%
“…The absorption band around 250 nm in the electronic spectra of styrene derivatives is allied to an allowed π→π* transition (substituted benzene K band), polarized along the long axis of the unsaturated chromophore. 48,49 By inspection of the molecular structure of dichromophoric derivatives 2 ( Fig. 6) and 7-9, it is apparent that the two interacting transition dipoles define a negative twist (negative chirality), in agreement with the negative exciton couplets observed in the experimental CD spectra (Figs.…”
Section: Conformational Analysis and Chiroptical Propertiessupporting
confidence: 65%
“…The absolute configuration of the separated enantiomers for selected dihydrofurocoumarin derivatives has been determined using the exciton coupling chirality method [8]. It has been shown that the first eluted peak on the Chirobi-652 Fig.…”
Section: Absolute Configuration Determination and Enantiomer Elution mentioning
confidence: 99%
“…Recently, different chiral dihydrofurocoumarins have been isolated as natural products, and shown to be active against a number of diseases [7]. For example, marmesin and columbionetin derivatives have been shown to exhibit cytotoxicity against KB cells, to inhibit c-AMP (which affects coronary vasodilation) and to mediate the action of acetylcholinesterase (which plays a role in Alzheimer's disease) [4,5,6,7,8,9]. Dihydrofurocoumarins appear to be nontoxic [4,10,11,12].…”
Section: Introductionmentioning
confidence: 99%